“Death audit is a fight” – provider perspectives on the ethics of the Maternal and Perinatal Death Surveillance and Response (MPDSR) system in Ethiopia - Kaya Cetin; Dawit Worku; Asrat Demtse; Andrea Melberg; Ingrid Miljeteig (BMC Health Services Research, 2022)
Abstract Background Maternal and neonatal health are regarded as important indicators of health in most countries. Death auditing through, for example, the Maternal and Perinatal Death Surveillance and Response (MPDSR) is viewed as key to preventing maternal and newborn mortality. However, little is known about the implications of implementing perinatal auditing for healthcare professionals in low-income contexts. This study aimed to explore the ethical and practical consequences clinicians experience concerning MPDSR reporting practices in Ethiopia.  Methods Qualitative semi-structured in-depth individual interviews were conducted with 16 healthcare workers across professions at selected facilities in Ethiopia. The interview questions were related to clinicians’ experiences with, and perceptions of, death auditing. Their strategies for coping with newborn losses and the related reporting practices were also explored. The material was analyzed following systematic text condensation, and the NVivo11 software was used for organizing and coding the data material. Results Participants experienced fear of punishment and blame in relation to the perinatal death auditing process. They found that auditing did not contribute to reducing perinatal deaths and that their motivation to stick to the obligation was negatively affected by this. Performing audits without available resources to provide optimal care or support in the current system was perceived as unfair. Some hid information or misreported information in order to avoid accusations of misconduct when they felt they were not to blame for the baby’s death. Coping strategies such as engaging in exceedingly larger work efforts, overtreating patients, or avoiding complicated medical cases were described. Conclusions Experiencing perinatal death and death reporting constitutes a double burden for the involved healthcare workers. The preventability of perinatal death is perceived as context-dependent, and both clinicians and the healthcare system would benefit from a safe and blame-free reporting environment. To support these healthcare workers in a challenging clinical reality, guidelines and action plans that are specific to the Ethiopian context are needed.